As A Living Culture of Traditional Herbal Coffee in Turkey: Chickpea Coffee - Muhammet Akkaya; Ernaz Altundağ-çakır; Ece Sevgi; Çağla Kızılarslan-hançer (Düzce Üniversitesi Bilim ve Teknoloji Dergisi, 2019)
It is generally preferred to use of plant species that have a natural spread in a region as a beverage. It is known that, different plants are used in making herbal coffee in our country. Especially in times of war and for economical reasons, it was not possible for our people to reach a cup of coffee made from coffee beans, and in such cases it was tried to benefit from different plants. Chickpea (Cicer arietinum L., known as “nohut” in Turkish), which is a member of the Fabaceae family, is one of the most important legumes as a source of vegetable protein and one of those herbal coffees. In this study we compiled the information we obtained about chickpea coffee such as how to make it, how to serve it and its features etc. in Işıkeli village of Biga (Çanakkale). We believe that, this study will contribute to the survival of the chickpea coffee tradition as the traditional usage of chickpea is about to disappear nowadays.